Individual differences in response to positive and negative stimuli: endocannabinoid-based insight on approach and avoidance behaviors - Laricchiuta, Daniela; Petrosini, Laura (Frontiers in Systems Neuroscience, 2014)
Approach and avoidance behaviors - the primary responses to the environmental stimuli of danger, novelty and reward - are associated with the brain structures that mediate cognitive functionality, reward sensitivity and emotional expression. Individual differences in approach and avoidance behaviors are modulated by the functioning of amygdaloid-hypothalamic-striatal and striatal-cerebellar networks implicated in action and reaction to salient stimuli. The nodes of these networks are strongly interconnected and by acting on them the endocannabinoid and dopaminergic systems increase the intensity of appetitive or defensive motivation. This review analyzes the approach and avoidance behaviors in humans and rodents, addresses neurobiological and neurochemical aspects of these behaviors, and proposes a possible synaptic plasticity mechanism, related to endocannabinoid-dependent long-term potentiation and depression that allows responding to salient positive and negative stimuli.